2015
DOI: 10.1093/brain/awv150
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of glatiramer acetate and grafted CD115+monocytes in a mouse model of Alzheimer’s disease

Abstract: Weekly glatiramer acetate immunization of transgenic mice modelling Alzheimer's disease resulted in retained cognition (Morris water maze test), decreased amyloid-β plaque burden, and regulation of local inflammation through a mechanism involving enhanced recruitment of monocytes. Ablation of bone marrow-derived myeloid cells exacerbated plaque pathology, whereas weekly administration of glatiramer acetate enhanced cerebral recruitment of innate immune cells, which dampened the pathology. Here, we assessed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
177
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(190 citation statements)
references
References 70 publications
12
177
0
Order By: Relevance
“…Curcumin is a natural and safe fluorochrome that crosses the blood-brain and -retinal barriers and binds to Aβ fibrils and oligomers with high affinity [490, 527, 538551], with the ability for ex vivo and in vivo visualization when specifically bound to retinal Aβ plaques (Figure 7A–B) [485, 490, 527]. This approach enabled non-invasive detection and monitoring of desecrate retinal Aβ deposits in live animal models of AD [490], including the capability to track the dynamic appearance and clearance of individual plaques and their substantial reduction after glatiramer acetate (GA) immunotherapy [527, 552, 553]. …”
Section: Contribution and Role Of Retinal Imagingmentioning
confidence: 99%
“…Curcumin is a natural and safe fluorochrome that crosses the blood-brain and -retinal barriers and binds to Aβ fibrils and oligomers with high affinity [490, 527, 538551], with the ability for ex vivo and in vivo visualization when specifically bound to retinal Aβ plaques (Figure 7A–B) [485, 490, 527]. This approach enabled non-invasive detection and monitoring of desecrate retinal Aβ deposits in live animal models of AD [490], including the capability to track the dynamic appearance and clearance of individual plaques and their substantial reduction after glatiramer acetate (GA) immunotherapy [527, 552, 553]. …”
Section: Contribution and Role Of Retinal Imagingmentioning
confidence: 99%
“…This was later confirmed by Naert and colleagues [59]. More recent reports showed that cells expressing monocyte markers are associated with plaques in two transgenic models of Aβ deposition [60], and that adoptively transferred monocytes home in to these plaques [61]. Furthermore, while CD36 is expressed in microglial cells, its level of expression on peripheral monocytes and macrophages is more than 100-fold higher than in microglial cells [16].…”
Section: Open Questions and Caveatsmentioning
confidence: 81%
“…Among the family of matrix metalloproteinases (MMP), MMP-9 and MMP-8 are important for the migration of microglia during embryogenesis [3]. Expressed MHC class II [41] Highly expressed MHC class II [21] Expressed MHC class II [42] Neurotoxicity Produced pro-inflammatory cytokines [43] Produced pro-inflammatory cytokines [44] Produced pro-inflammatory cytokines (in brain) [45] Increased ROS [16,46] Reduced ROS [16] Reduced ROS (in brain) [47] Produced nitric oxide [48] Expressed the inducible form of nitric oxide synthase (in brain) [49] Produced nitric oxide [42] Phagocytosis Dead photoreceptors and cell debris (dead cells in brain) [50,51] Unclear Dead photoreceptors and cell debris [50] Living stressed photoreceptors (living neurons in brain) [52,53] Unclear Unclear Amyloid deposits clearance Impaired Aβ clearance and facilitated Aβ deposition [16] Increased Aβ clearance [14,16] Increased Aβ clearance [54] Neuroprotection Produced neurotrophic factors [55] Unclear Produced neurotrophic factors [15] Unclear Unclear Produced anti-inflammatory cytokines [56] Vascularization Promoted the formation of CNV (VEGF, PDGFβ, and ICAM) [55] Pathological neovascularization (IL-1β) [44,57] Promoted the formation of CNV [58] Unclear Physiological neovascularization [59] Unclear…”
Section: Origin and Distribution Of Microglia During Development Ys Amentioning
confidence: 99%